Assessing the effect of split and additional late N fertilisation on N economy of maize - Maltese, Nicolás; Carciochi, Walter Daniel; Caviglia, Octavio; Sainz Rozas, Hernan Rene; García, Mauricio; Lapaz, Adrián; Ciampitti, Ignacio; Reussi Calvo, Nahuel Ignacio (Elsevier, 2024)
Context: In the temperate-humid region of Argentina, nitrogen (N) fertilisers in maize (Zea mays L.) are mainly applied around sowing, whereas N-splitting is rare and occurs during early vegetative stages. Splitting and late N fertilisation, even up to silking (R1), effects on yield have been recently studied. However, to the extent of our knowledge, these studies have mainly focused on the effect of these strategies on maize yield, but less on the crop N economy. Objective: The aims were to study the mechanisms explaining the effect of i) splitting N and ii) additional N application at R1 on yield, post-flowering N uptake, kernel weight, N uptake efficiency, and the relationship of these variables with the N nutrition index (NNI). Methods: Seven experiments were carried out throughout the humid temperate region of Argentina, evaluating seven treatments: a control without N fertilisation, N rate entirely applied at sowing or split between sowing, eight leaf (V8), and R1, an additional N rate at R1, and an N sufficiency treatment. Results: The scenario with split N application had no adverse effect on either yield or N uptake at maturity (P > 0.05), with less pre-flowering N uptake compensated with more post-flowering N uptake in late N applications. In turn, increases in both yield and kernel weight were related to increases in post-flowering N uptake. Positive yield responses to N-splitting (plateauing at 450 kg ha-1) were obtained with yield responses to N greater than 3107 kg ha-1. Likewise, yield responses to additional N at R1 (plateauing at 1107 kg ha-1) were evident with yield responses greater than 2943 kg ha-1. The NNI at R1 accounted for variations in post-flowering N uptake and yield, as well as yield responses to additional N at R1 and their impact on kernel weight. Conclusion: Results show that N-splitting and late N fertilisation are promising strategies that, combined with crop N status monitoring, could lead to improvements in both maize yield and N economy.